The Status of Libraries and Information Centres in Namibia - S. Negumbo (Библиосфера, 2024)
In an increasingly interconnected world, understanding of cultures, traditions and systems of different countries is of growing importance. This article aims to acquaint readers of this journal with library systems in Namibia, shedding more light on its goals, history, and various branches such as the National Library of Namibia, the National Archives of Namibia, as well as special, academic, and school libraries. Through statistical data on services offered and user demographics, the author provides insights into the current landscape of libraries in Namibia. Additionally, the article addresses challenges faced by these institutions, ultimately concluding that while the library systems in Namibia has made significant strides since Namibia gained independence, further efforts are required for its continued development and enhancement.